1976
DOI: 10.1017/s0003356100031044
|View full text |Cite
|
Sign up to set email alerts
|

Fat distribution in steer carcasses of different breeds and crosses. 1. Distribution between depots

Abstract: SUMMARYDissection data from 643 carcasses of castrated male cattle (steers) of 15 breed-type × feeding system groups were used to examine the distribution of total fat (TF) between subcutaneous (SF), intermuscular (IF), kidney knob and channel (KKCF) and cod fat depots. The breed-type groups, which were from cereal or grass/cereal feeding systems, included Ayrshire, Simmental × Ayrshire, British Friesian and Friesian crosses with Aberdeen Angus, Hereford, Limousin, Charolais, South Devon and Simmental. Means f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
39
1
1

Year Published

1978
1978
2001
2001

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(49 citation statements)
references
References 7 publications
8
39
1
1
Order By: Relevance
“…Smaller steers, however, started to deposit fat at an early age and lighter weights than the larger ones, and differences in fat distribu tion were suggested when the amount of fat in each depot was adjusted to a constant total dissectible fat in the body (Tables 6 and 7). Kempster et al(1976a) also found consid erable variation in fat distribution among breeds of different biological types at the same level of fatness.…”
Section: Resultsmentioning
confidence: 74%
See 3 more Smart Citations
“…Smaller steers, however, started to deposit fat at an early age and lighter weights than the larger ones, and differences in fat distribu tion were suggested when the amount of fat in each depot was adjusted to a constant total dissectible fat in the body (Tables 6 and 7). Kempster et al(1976a) also found consid erable variation in fat distribution among breeds of different biological types at the same level of fatness.…”
Section: Resultsmentioning
confidence: 74%
“…Kempster et al (1976a), working with differ ent breeds, and Berg et al (1978a), using cattle of the three sexes, reported an increase in the ratio of subcutaneous: intermuscular fat with fattening. The discrepancies may be explained by differences in the cattle used and by the inclu sion of omental and mesenteric fat depots in our study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…At slaughter, the effect of a change in P8 fat depth had a greater impact on RBY for Angus and Murray Grey animals than was the case for Herefords and Shorthorns, which most likely reflect differences in fat distribution and partitioning between the breeds. Research by Kempster et al (1976) supports the conclusion that animals of different breeds display different fat distribution patterns, which are not described by measurements of fat depth at only 1 site.…”
Section: P8 Fat Depthmentioning
confidence: 74%